Acute Responses Of A Drop-Set Session On Muscular Activation And Its Applicability In Resistance- Trained Individuals - Bernardo Ide; Pedro A. B. Fonseca; René Brenzikofer; Leonardo H. F. Carvalho; Evanisi T. Palomari; Denise V. Macedo (International Universities Strength and Conditioning Association, 2023)
We investigated whether performing repetitions to muscular failure (FAIL) during a drop-set would affect muscle activation in trained individuals. Twelve young men performed a drop-set session consisting of 3 sets of two intensity drops (80 to 60 and to 40% of one-repetition maximum [1-RM]) load in a leg press machine. Linear regression between the quadriceps femoris root mean square of surface electromyography (EMGRMS) was employed to observe the initial muscle activation (intercept) and its behavior over the repetitions (slope). The EMGRMS intercept of the first set decreased (p<0.05) according to load reduction (136.8±4.8 at 80%1-RM to 119.3±5.5 and 110.6±5.5 at 60 and 40%1-RM, respectively). Slopes different from zero (p<0.05) were observed at 80 and 60%1-RM during the first set. Remarkably, during the second and third sets, we observed an increased EMGRMS intercept at 60%1-RM (p<0.05), leading to non-significant (p>0.05) differences compared to 80%1-RM. The maximum initial muscle activation occurred at higher loads only, but low loads performed to FAIL may be necessary for increasing and maintaining muscle activation at higher loads. Understanding these acute responses may support coaches and athletes in optimizing strength training responses during drop-set sessions into their periodization.